A critical analysis of governance and management in Zimbabwe's colleges of technical and vocational education: issues for revitalisation - Mbizvo, Washington T (Rhodes University, Faculty of Education, Department of Education, 2003)
This research was carried out in order to gain a better understanding of the practice of governance in a technical or vocationally oriented college and the critical role played by the principal as a college manager within the governance system in which industrialists and head office are also key players. Conceptual literature relating to issues of governance and management within the education scenario is examined. The wider issues of governance are critically analysed in the context of power and control mechanisms initiated by the Ministry of Higher Education as the responsible authority for the colleges. The influence of the industrial sector as the consumers of skilled labour force is analysed through college advisory councils set up in terms of the relevant pieces of legislation. The research is qualitative and takes the form of three case studies of technical and vocational colleges in Zimbabwe. Data were collected through multiple methods from varied sources with a view to ensuring triangulation. The multiple-case design enabled me to dig beneath the surface of what apparently happens in these organisations and unearth issues and concerns at the wider governance and management levels. Views and experiences of participants are captured and explained through in-depth interviews, observations and documentary sources. Results are discussed in relation to the relevant literature allowing grounded theory to emerge. The research highlights the roles of key players in governance and the issues of relationships among these actors. What emerges is a desperate situation of ineffectiveness, problematic processes in governance and poor responsiveness of these colleges to the labour market demands. The potential for generalisability and transferability is discussed in the report and possible corrective intervention strategies are recommended. The thesis demonstrates that managers of these colleges and indeed senior officers in head office who are at the centre of governance and will need transformational leadership development in order for them to come to terms with such things as people's feelings, abandoning 'outdated' policies, managing change, and handling communication effectively. Various strategies for revitalisation of governance and management in technical and vocational colleges are suggested.
Keywords: Education, Higher -- Zimbabwe; Universities and colleges -- Zimbabwe; Universities and colleges -- Zimbabwe -- Administration; Vocational education -- Zimbabwe; Technical education -- Zimbabwe